Effects of Magnesium Sulfate on Pain, Nausea/Vomiting, and Anesthetic Consumption after Corneal Transplantation and Vitrectomy - Mojtaba Rahimi-Varposhti; Darioush Moradi-Farsani; Aneseh Salehnia; Kamran Montazeri; Amir Shafa (مجله دانشکده پزشکی اصفهان, 2017)
Background: Pain and postoperative nausea/vomiting (PONV) are of the most frequent complications after major ophthalmologic surgeries, and there is no general agreement on the effective method of controlling them. We compared the effects of magnesium sulfate on pain, nausea/vomiting, and anesthetic and analgesic requirement after corneal transplantation and vitrectomy surgeries.